Modelo biodinâmico para medição da transmissibilidade assento-à-mão da vibração de corpo inteiro - Herbert Câmara Nick (2022)
This work aims to develop a biodynamic model in Altair® Motion View software representing four degrees of freedom of the human body sitting on a vibrating platform for testing human vibrations to obtain seat-to-hand transmissibility in the vertical direction of the z axis that is, in the longitudinal direction of the human body. To validate the proposed biodynamic model, tests were carried out, a priori, using a vibrating platform in order to submit a group of 20 volunteers to Whole Body Vibration (WBV) exposure in the vertical direction ("z" axis) of excitation, being: 10 volunteers exposed to 5 Hz with acceleration of 0.2 m/s² during 1.2 min and with acceleration of 0.5 m/s² during 3 min; and another 10 volunteers exposed to 30 Hz with an acceleration of 0.2 m/s² during 1.2 min and with an acceleration of 0.5 m/s² during 3 min, experimentally, as an input signal of the WBV excitation. For the input acceleration measurement, a uniaxial accelerometer was used on the seat and for the output signal, a triaxial accelerometer was used in the volunteer's right hand, according to the instructions of the international standards ISO 2631-1:1997 and ISO 5349-1:2001. A linear model with four degrees of freedom was developed to represent the biodynamic behavior of individuals submitted to longitudinal WBV and in the conditions presented in a human body seated on the vibration platform. The curve generated from the model curve and the experiment curve converged to similar values, which means the representation of a significant fit between the two curves, given the results obtained from the correlation coefficient of curves and the graphs plotted by MATLAB®. The transmissibility (Tr) calculated experimentally for the excitation parameters had the same attenuation or amplification behavior as the proposed model, which can be seen by the boxplot plots generated by IBM® SPSS Statistics. It was noticed that the frequency is more impacting variable on the transmissibility than the amplitude of acceleration. With this, it is concluded that using simplified biodynamic models representative of the human body can represent, with significant results, real situations of experiments, taking into account the differences in biomechanical parameters.